Evaluasi Skor Pre-Test dan Post-Test Peserta Pelatihan Pelayanan Kontrasepsi bagi Dokter dan Bidan di Fasilitas Pelayanan Kesehatan di BKKBN Provinsi Jawa Tengah - febrina suci hati (Jurnal Edutrained : Jurnal Pendidikan dan Pelatihan, 2023)
This study aims to evaluate pre-test and post-test results of participants in Contraceptive Service Training for Doctors and Midwives in Health Care Facilities for BKKBN representatives in Central Java. Research method used in this study is the quantitative method. The data used is the primary data obtained from the pre- and post-test scores of 90 respondents. During this time, the data analysis techniques used were descriptive analysis and paired t-test. Through the paired sample t-test, it is known that the significance value (p-value) for the pretest and posttest data is 0.000 ((<0.05). This shows that there is a statistically significant difference between pre-test and post-test results for Contraceptive Service Training for Doctors and Midwives in Health Care Facilities participants. Therefore, we can conclude that the knowledge of the participants are increasing after participating in the Contraceptive Service Training for Doctors and Midwives in Health Care Facilities